Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Dalam Membayar Pbb Daerah Jakarta Barat - Angelina Jessica Hirawan, Widyasari (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This study aims to determine the effect of tax knowledge, tax sanctions, and SPPT on taxpayer compliance in the payment of land and building tax in the West Jakarta area.. The design of this study uses quantitative and causal methods. The sampling technique uses non-probability sampling and the sample selection technique uses purposive sampling, with 150 respondents namely taxpayers who already own land and buildings in the West Jakarta area.. Data collection techniques using a questionnaire. The analysis used is SPSS application software version 23. Overall the results of this study indicate that tax knowledge has a significant positive effect on taxpayer compliance in the payment of land and building tax in the West Jakarta area, tax sanctions have a significant positive effect on taxpayer compliance in the payment of land and building tax in the West Jakarta area, and SPPT has a significant positive effect on taxpayer compliance in the payment of land and building tax in the West Jakarta area.